E-waste : problems, Islamic perspective and solutions - Faris, Waleed Fekry; Khalifa, Othman Omran; Hawari, Muaz (IIUM Press, 2011)
Although electronic waste (e-waste) seems to have only recently become a problem. this issue has been building since the electronic products and computers were first manufactured. Electronic wvaste includes broken or obsolete televisions, computer monitors, central processing units, phones, videocassette recorders, copiers and printers, stereos and speakers, microwaves, and other electronic equipment. As a general category, e-waste may contain significant amounts of heavy metals and other hazardous materials. Consumer electronics devices contain many toxic materials that can have detrimental impact on public health and the environment, if improperly disposed. The life span of computers used to be decades, then years, and now often months. millions of computers, screens, and peripherals are being rendered obsolete after little more than a year of active use. Just a small percentage of these are reaching the solid waste stream. Most are stored in attics, garages, and warehouses, their owners unwilling to throwaway something they perceive to have so much value. Most consumers are unaware of the toxic materials in the products they rely on for word processing, data management, and access to the internet, as well as for electronic games. In generaL computer equipment is a complicated assembly of more than 1,000 materials, many of which are highly toxic, such as chlorinated and brominated SUbstances, toxic gases, toxic metals, biologically active materials, acids, plastics and plastic additives